The Impact Of Project-Based Learning (PJBL) On The Development Of Critical Thinking Capabilities In Islamic Religious Education At SMPIT Khairunnas, Bengkulu City - Mardhatillah, Mardhatillah; Firmasari, Desi; Febriana, Lety; syubli, syubli (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The impact of the PJBL approach on critical thinking abilities is investigated in this study. This study employs an experimental research design, which is a sort of quantitative research. The study’s findings demonstrate that H0 is rejected and Ha is accepted. Because SMPIT Khairunnas Bengkulu City students are accustomed to traditional learning, they may find it difficult or even impossible to comprehend the PJBL method’s learning system. This could lead to the emergence of laziness in learning activities, which could ultimately lower the students’ critical thinking abilities at SMPIT Khairunnas Bengkulu City.